1998
DOI: 10.1183/09031936.98.12030612
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils induce damage to respiratory epithelial cells infected with respiratory syncytial virus

Abstract: The mechanisms by which respiratory syncytial virus (RSV) infection induces bronchiolitis and airway disease are unclear. The presence of large numbers of polymorphonuclear leukocytes (PMN) in the airways of infants with RSV infection suggests a potential role of PMN in airway injury associated with RSV infection. To investigate the potential role of neutrophils in RSV bronchiolitis, human alveolar type II cells (A549 cells) were infected with different doses of RSV for 6-48 h. A 51Cr-releasing assay was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
71
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 28 publications
14
71
0
1
Order By: Relevance
“…It has been reported that RSV infection of respiratory epithelial monolayers can promote neutrophil adherence which could, in turn, potentially contribute to the airway injury and obstruction that accompanies bronchiolitis [9]. Our recent studies show that neutrophils augment the damage to respiratory epithelial cells induced by RSV infection in vitro [10]. The modulation of neutrophil apoptosis in RSV infection in vivo may regulate the epithelial damage induced by neutrophils.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…It has been reported that RSV infection of respiratory epithelial monolayers can promote neutrophil adherence which could, in turn, potentially contribute to the airway injury and obstruction that accompanies bronchiolitis [9]. Our recent studies show that neutrophils augment the damage to respiratory epithelial cells induced by RSV infection in vitro [10]. The modulation of neutrophil apoptosis in RSV infection in vivo may regulate the epithelial damage induced by neutrophils.…”
Section: Introductionmentioning
confidence: 76%
“…The accelerated neutrophil apoptotic process in vivo may limit the release of neutrophil contents from disintegrating cells in the airways in RSV bronchiolitis [8] and prevent further injuries to the epithelial cells induced by neutrophils in RSV infection [4,10]. On the other hand, because apoptotic neutrophils are functionally impaired [32], accelerated neutrophil apoptosis in vivo may contribute to the risk of secondary infection [11], which has been associated with RSV infection [33,34].…”
mentioning
confidence: 99%
“…Leukocyte populations of the connecting airway in severe RSV infection are typically composed of neutrophils, and they participate in the viral immunopathology [34]. Epithelial sloughing and necrosis is, in part, a direct result of neutrophil adhesion and exocytosis [35]. RSV infection of epithelial cells and monocytes leads to a synergistic up-regulation in expression of interleukin-8 (IL-8), a CXC chemokine that enhances neutrophilic chemotaxis, and enhanced IL-8 expression is correlated with severe RSV infection [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a neutrophil-rich exudate detected by bronchoalveolar lavage has been described (13). These polymorphonuclear neutrophil granulocytes (PMN) adhere to the RSV-infected epithelial cells and become activated thereby (14,15). As a consequence, they release reactive oxygen radicals and hydrolytic enzymes and, therefore, are responsible primarily for the subsequent intense inflammation of the lung (16,17).…”
Section: And Wolfgang Königmentioning
confidence: 99%
“…For the synthesis of cDNA, prepared total RNA (2 g) was mixed with Moloney murine leukemia virus reverse transcriptase buffer (3 mM MgCl 2 , 75 mM KCl, 50 mM Tris-HCl; Life Technologies), 0.5 mM deoxyribonucleoside triphosphates (dNTP-Set; Life Technologies), 1 U/ l RNase inhibitor (Amersham), 4 U/ l Moloney murine leukemia virus reverse transcriptase (Life Technologies), and 2.0 ng of oligo(dT) [12][13][14][15][16][17][18] in a volume of 50 l. The synthesis of cDNA was done by heating at 37°C for 60 min. The cDNA was stored at Ϫ20°C.…”
Section: Rt-pcr Analysis Of Icam-1mentioning
confidence: 99%